Hubungan kepatuhan konsumsi pemberian makanan tambahan (PMT) dengan status gizi berat badan menurut umur (BB/U) pada balita underweight - Wilujeng, Sindy; Rakhma, Luluk Ria; Kisnawaty, Sudrajah Warajati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Nutritional problems in children under five, particularly underweight cases, remain a major public health challenge in Indonesia with significant impacts on child development. In 2019, the prevalence of underweight (weight-for-age) among children under five in Indonesia reached 17.1%, while in Sukoharjo Regency it was recorded at 11.8%. Compliance with the supplementary feeding program is an important strategy to address this issue. Purpose: To analyze the relationship between compliance with consumption of supplementary feeding and nutritional status (W/A) in underweight toddlers. Method: A cross-sectional design was used, involving 104 underweight children under five from a total population of 228, selected by simple random sampling. Primary data were collected through interviews with parents, while secondary data were obtained from Mojolaban Health Center. Body weight was measured using a digital scale and calculated into weight-for-age Z-scores (W/A), while compliance was assessed using weekly comstock monitoring. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Results: The majority of mothers were aged 26–35 years (69.2%), unemployed (73.1%), had incomes above the minimum wage (52.9%), and had a high school education (57.7%). Compliance with supplementary feeding was low (17.3%). After the intervention, 60.6% of toddlers gained weight and 19.3% had normal nutritional status, but statistical analysis (p=0.101) showed no significant relationship between compliance with supplementary feeding and nutritional status. Conclusion: There was no significant relationship between compliance with supplementary feeding and nutritional status (weight-for-age) in underweight toddlers. Suggestion: The quality of additional food consumed, frequency of illness, and daily food consumption are several other factors that can influence the nutritional status of toddlers and need to be included in further research. Keywords: Adherence; Nutritional Status; Supplementary Feeding; Underweight. Pendahuluan: Masalah gizi pada balita, khususnya kasus underweight, masih menjadi tantangan kesehatan masyarakat di Indonesia dengan dampak signifikan terhadap perkembangan anak. Pada tahun 2019, prevalensi balita underweight (berat badan menurut umur) di Indonesia mencapai 17.1%, sementara di Kabupaten Sukoharjo tercatat sebesar 11.8%. Kepatuhan terhadap program Pemberian Makanan Tambahan (PMT) menjadi strategi penting untuk mengatasi masalah ini. Tujuan: Untuk menganalisis hubungan kepatuhan konsumsi PMT dan status gizi (BB/U) pada balita underweight. Metode: Penelitian dengan desain cross-sectional yang melibatkan 104 balita underweight dari populasi 228, dipilih secara simple random sampling. Data primer diperoleh melalui wawancara orang tua, sedangkan data sekunder dari Puskesmas Mojolaban. Berat badan diukur dengan timbangan digital dan dihitung Z-score BB/U, kepatuhan dinilai dari comstock mingguan. Analisis menggunakan uji Chi-Square dengan p < 0.05. Hasil: Mayoritas ibu berusia 26–35 tahun (69.2%), tidak bekerja (73.1%), berpendapatan di atas UMR (52.9%), dan berpendidikan SMA (57.7%). Tingkat kepatuhan konsumsi PMT rendah (17.3%). Setelah intervensi, 60.6% balita naik berat badan dan 19.3% berstatus gizi normal, namun uji statistik (p=0.101) menunjukkan tidak ada hubungan signifikan antara kepatuhan PMT dan status gizi. Simpulan: Tidak terdapat hubungan yang signifikan antara kepatuhan mengonsumsi PMT dengan status gizi berat badan menurut umur (BB/U) pada balita underweight. Saran: Kualitas makanan tambahan yang dikonsumsi, frekuensi sakit, dan konsumsi makanan sehari-hari merupakan beberapa faktor lain yang dapat memengaruhi status gizi balita dan perlu diikutsertakan dalam penelitian selanjutnya. Kata Kunci: Kepatuhan; Pemberian Makanan Tambahan (PMT); Status Gizi; Underweight.